Testing pluralism : globalizing belief, localizing gods - Giordan, Giuseppe.; Swatos, William H. (Religion and the Social Order, 2013)
This volume of the Religion and the Social Order series examines the phenomenon of the globalization of religions that has particularly characterized the last fifty years. Historically, religions were relatively tightly connected with territoriality. The advent of relatively inexpensive and relatively accessible air transport has made it possible for groups of significant size to move from their original homelands and resettle in new sites. In contrast to predictions associated with secularization theories that dominated the middle of the twentieth century, today we find that the world's religions continue to provide meaning and value in the lives of their adherents. This volume examines at a global level a variety of such groups and their adjustments.